Small bowel intussusception secondary to intestinal submucosal cyst in an infant - Seiichiro Inoue; Akio Odaka; Yuki Muta; Shohei Maruta; Yuta Takeuchi; Yoshifumi Beck; Takahisa Yamashita (Elsevier, 2022)
We experienced an infant with small bowel intussusception due to a rare pathological lead point. The two-month-old baby has admitted to our center with because of vomiting and bloody stool. Although an intraabdominal multicystic mass was suspected by abdominal ultrasonography, other examinations did not detect any abnormal findings. The infant was discharged but was readmitted one week later because of vomiting and transient impairment of consciousness. Although no ileocolic intussusception was visible by enema, abdominal computed tomography and ultrasonography clearly showed intestinal invagination. Emergency laparotomy was performed, whereupon a small bowel intussusception was observed. After surgical reduction, a small, palpable intramural mass was found at the lead point of the invagination, and the section of the intestine containing the mass was removed by wedge resection. The mass was multicystic and was diagnosed by immunohistochemistry as an intestinal submucosal cyst.